Nonsurgical Management of Cartilage Defects of the Knee: Who, When, Why, and How? - Hanaoka, Chad; Fausett, Cameron; Jayabalan, Prakash (The Journal of Knee Surgery, 2020)
The nonoperative practitioner managing individuals with cartilage defects should use a patient-centered, multifaceted approach that aims to individualize treatment to provide optimal benefit. These include addressing modifiable risk factors for disease progression and instituting interventions such as weight loss, nutrition, physical activity, and potentially regenerative medicine strategies. This review will focus on these nonoperative treatment strategies with a focus on when treatments are necessary, who will benefit from these approaches, why they are specifically appropriate, and, finally, how these treatments directly modify the structure of a patient's cartilage and resulting symptoms.
Keywords: cartilage; osteoarthritis; knee